Synthetic Approaches to the Bifunctional Chelators for Radionuclides Based On Pyridine-Containing Azacrown Compounds - Zubenko, Anastasia D.; Shchukina, Anna A.; Fedorova, Olga A. (Synthesis, 2020)
Synthetic ways to introduce functional groups (CO2Me, CO2H, OCH2CO2H, OCH2C≡CH, CH2OH, CH2Cl, CH2N3) into the pyridine ring of pyridine-containing azacrown compounds are described. These groups were introduced at position-4 of the pyridine ring, while keeping the macrocyclic carboxylate groups available for metal chelation. The derivatives were obtained by macrocyclization reaction of 4-substituted, trimethyl pyridine-2,4,6-tricarboxylate or by modification of methyl ester group in pyridine fragment of macrocycles. Obtained derivatives can be applied for preparing radiotherapeutic agents by conjugation to different vector biomolecules for targeted drug delivery to cancer cells without damaging healthy tissue.
Keywords: bifunctional chelators; azacrown compounds; macrocyclization; radiopharmaceuticals; bioconjugation